Temporal and spatial changes in rhizosphere bacterial diversity of mountain Rhododendron mucronulatum - Wang, Sirui; Zhou, Tiantian; Zhao, Hewen; Zhang, Kezhong; Cui, Jinteng (Frontiers in Microbiology, 2023)
To better conserve the ecology of the wild Rhododendron mucronulatum range, we studied the rhizosphere microenvironment of R. mucronulatum in Beijing’s Yunmeng Mountain National Forest Park. R. mucronulatum rhizosphere soil physicochemical properties and enzyme activities changed significantly with temporal and elevational gradients. The correlations between soil water content (SWC), electrical conductivity (EC), organic matter content (OM), total nitrogen content (TN), catalase activity (CAT), sucrose-converting enzyme activity (INV), and urease activity (URE) were significant and positive in the flowering and deciduous periods. The alpha diversity of the rhizosphere bacterial community was significantly higher in the flowering period than in the deciduous period, and the effect of elevation was insignificant. The diversity of the R. mucronulatum rhizosphere bacterial community changed significantly with the change in the growing period. A network analysis of the correlations revealed stronger linkages between the rhizosphere bacterial communities in the deciduous period than in the flowering period. Rhizomicrobium was the dominant genus in both periods, but its relative abundance decreased in the deciduous period. Changes in the relative abundance of Rhizomicrobium may be the main factor influencing the changes in the R. mucronulatum rhizosphere bacterial community. Moreover, the R. mucronulatum rhizosphere bacterial community and soil characteristics were significantly correlated. Additionally, the influence of soil physicochemical properties on the rhizosphere bacterial community was larger than that of enzyme activity on the bacterial community. We mainly analyzed the change patterns in the rhizosphere soil properties and rhizosphere bacterial diversity of R. mucronulatum during temporal and spatial variation, laying the foundation for further understanding of the ecology of wild R. mucronulatum.